Moral Message-Based Deep Learning in Mathematics Instruction for Mathematics MGMP Teachers of Kubu Raya - Basuni, Bistari; Mikraj, Hamdani; Rustam, Rustam; Ahmad, Dian; Zubaidah, Zubaidah; Winarji, Agus; Nurfadilah, Nurfadilah; Pasaribu, Revi Lestari; Jamilah, Jamilah; Junarti, Junarti (International Journal of Public Devotion, 2025)
The seminar titled "Deep Learning Based on Moral Messages in Mathematics Learning" was conducted for mathematics teachers in the MGMP (Subject Teacher Forum) of Kubu Raya Regency as a response to the need for enhancing the quality of learning that emphasizes not only cognitive but also affective aspects. The concept of deep learning in this seminar was emphasized through three core principles: awareness, meaningfulness, and enjoyment. These principles aim to create reflective, contextual learning experiences that motivate students to think critically and develop deep, lasting understanding. In addition, the integration of moral messages in mathematics learning referred to Thomas Lickona’s theory, which includes moral knowing, moral feeling, and moral action as a comprehensive foundation for character education. Attended by 31 junior high school mathematics teachers, the seminar ran smoothly and was met with high enthusiasm. Questionnaire results showed that 93.7% of teachers agreed on the importance of deep conceptual understanding in learning, while 87.5% emphasized the importance of discipline and mutual respect in classroom interactions. These findings indicate strong teacher support for a holistic learning approach that fosters both conceptual mastery and moral character development among students.Deep Learning Berbasis Pesan Moral dalam Pembelajaran Matematika bagi Guru MGMP Matematika Kubu RayaABSTRAKSeminar bertajuk "Deep Learning Berbasis Pesan Moral dalam Pembelajaran Matematika" diselenggarakan untuk guru MGMP Matematika Kabupaten Kubu Raya sebagai respons terhadap kebutuhan peningkatan kualitas pembelajaran yang tidak hanya berfokus pada aspek kognitif, tetapi juga afektif. Konsep deep learning dalam seminar ini ditekankan melalui tiga prinsip utama, yaitu berkesadaran, bermakna, dan menggembirakan. Ketiganya bertujuan menciptakan pengalaman belajar yang reflektif, kontekstual, dan memotivasi siswa untuk berpikir kritis serta membangun pemahaman yang mendalam. Di sisi lain, penguatan pesan moral dalam pembelajaran matematika mengacu pada teori Thomas Lickona yang mencakup pengetahuan, perasaan, dan tindakan moral sebagai satu kesatuan dalam pembentukan karakter siswa. Seminar ini diikuti oleh 31 guru dan berlangsung lancar serta penuh antusiasme. Hasil angket menunjukkan bahwa 93,7% guru menyatakan pentingnya pemahaman konsep secara mendalam dalam pembelajaran, sementara 87,5% guru menilai sikap disiplin dan saling menghargai dalam lingkungan kelas sebagai aspek penting yang perlu ditanamkan. Temuan ini mengindikasikan bahwa guru sangat mendukung pendekatan pembelajaran yang holistik, yang tidak hanya menumbuhkan pemahaman konsep, tetapi juga membentuk karakter peserta didik secara menyeluruhKata Kunci :Deep Learning; Pesan Moral; Pembelajaran Matematika